Measuring Thailand’s Ocean Economy - Seenprachawong, Udomsak (Journal of Applied Economics and Management Strategy, 2023)
The objective of this paper is to measure Thailand’s ocean economy for the year 2018 by employing the Leontief Model. The ocean economy contains 12 sectors related to ocean based and coastal economic activities covering 23 coastal provinces in Thailand. It has been found that in 2018 Thailand’s ocean economy generates value added at 23.44 percent of the country’s GDP. Presently, only 3 major sectors are main drivers of Thailand’s ocean economy which accounts for 65.24 percent of the value added of the ocean economy. These sectors include offshore oil and gas, marine R&D and education, and marine and coastal tourism. The two sectors that should be focused for further development are marine and coastal tourism, and offshore oil and gas as they generate high value added and have high output multiplier values as well.